2023
DOI: 10.3390/ijms24065718
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Biological Investigation of the Platinum(IV) Tolfenamato Prodrug–Resolving Cisplatin-Resistance in Ovarian Carcinoma Cell Lines

Abstract: The research on the anticancer potential of platinum(IV) complexes represents one strategy to circumvent the deficits of approved platinum(II) drugs. Regarding the role of inflammation during carcinogenesis, the effects of non-steroidal anti-inflammatory drug (NSAID) ligands on the cytotoxicity of platinum(IV) complexes is of special interest. The synthesis of cisplatin- and oxaliplatin-based platinum(IV) complexes with four different NSAID ligands is presented in this work. Nine platinum(IV) complexes were sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…In addition to ASA, several commercial NSAIDs, such as ibuprofen, diclofenac, celecoxib and indomethacin, have been qualified as potential antitumor drugs, and some of them are in clinical trials for cancer treatment ( Sousa et al, 2023 ). Furthermore, conjugations of different NSAIDs ligands with platinum-based drugs (such as cisplatin- and oxaliplatin based platinum(IV) complexes) has been recently used to overcome platinum-resistance of ovarian cancer cells ( Barth et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ASA, several commercial NSAIDs, such as ibuprofen, diclofenac, celecoxib and indomethacin, have been qualified as potential antitumor drugs, and some of them are in clinical trials for cancer treatment ( Sousa et al, 2023 ). Furthermore, conjugations of different NSAIDs ligands with platinum-based drugs (such as cisplatin- and oxaliplatin based platinum(IV) complexes) has been recently used to overcome platinum-resistance of ovarian cancer cells ( Barth et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…17) bearing several fenamate ligands (mefenamic acid, flufenamic acid, tolfenamic acid) and conjugates 15-17 bearing felbinac, an active metabolite of fenbufen. 53 Cytotoxicity was assessed in A2780, A2780/cisR, SKOV3 and SKOV3/cisR cell lines. Although further studies were only pursued with a cisplatin derivative, compound 17 showed comparable toxicities to those of oxaliplatin and notably less cross-resistance with cisplatin.…”
Section: Enhancing Antitumoral Activity and Overcoming Resistancementioning
confidence: 99%
“…Cisplatin, oxaliplatin and carboplatin are the most popular platinum(II) cores used to generate platinum(IV) scaffolds in many studies, and each have been coordinated to various enzymatic inhibitors that supress cancer development and progression [28,36]. In particular, the coordination of non-steroidal anti-inflammatory drugs (NSAIDs) to the cores of cisplatin and its derivatives have resulted in chemo-anti-inflammatory prodrugs that are capable of reversing chemoresistance because of enhanced bioavailability [37][38][39][40][41]. Since the 1970s, NSAIDs have been extensively administered to cancer patients, simply for cancer pain management, but there was also a growing curiosity as to whether the regular ingestion of NSAIDs would help combat cancer and decrease cancer risk [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%